Designing a STAD based differentiated e-module to enhance instructional quality in digestive system with qur’anic integration - Susanti; Wulandari, Martha; Helmita, Roza; Fajar, Najmiatul; Fitri, Dwi Rini Kurnia; Haviz, M. (Universitas Negeri Jakarta, 2025)
This development research aims to produce valid and practical e-modules based on Differentiated Instruction using the STAD model, integrating Al-Qur'an content in the Digestive System topic. This type of research is development research (R&D) using the 4D model (define, design, develop and dissaminate), but the research was limited to the development stage due to constraints in time and funding. This research was conducted in grade XI of senior high school during the 2024/2025 school year. The sample in this study were class XI students totaling 33 people. The e-module was designed using the Canva application then converted using heyzine flipbook and liveworksheets for student worksheets, after completion of the e-module design, it was assessed by material, media and language and design validators using an instrument in the form of a validation questionnaire. The e-module was then tested on a small group to see the level of practicality of the product using the teacher and student response sheet instrument. The sheets were then analyzed using the percentage validation and practicality formulas. Data collection was obtained from the results of the validator questionnaire and student respondents. The results of the study showed that the resulting e-module was very valid with a validation score of 86% and very practical with a response percentage of educators at 100% and students at 89%. Based on the responses of the educator and student questionnaires, the e-learning module is categorized as highly practical and can be used in the learning process.